The prevalence of computer-related musculoskeletal complaints in female college students. - Hamilton AG; Jacobs K; Orsmond G (Work, 2005)
PURPOSE: The purpose of this study was to determine the prevalence of computer-related musculoskeletal complaints in female college students. This research also explored whether the number of hours per day spent using a computer, type of computer used (laptop vs. desktop), or academic major was related to the presence of musculoskeletal complaints. Additionally, 'job strain', a measure of job stress which can affect the physical health of an individual, was measured to determine whether students feel stress from the job of 'student' and if so, whether it contributed to these complaints. METHODS: Two surveys, The Boston University Computer and Health Survey and the Job Content Questionnaire [9], were distributed to 111 female college students to measure musculoskeletal complaints and job strain. Seventy-two surveys were returned. Chi-square and logistical regression were used to analyze the data. RESULTS: The results indicated that 80.6% of the participants reported computer-related musculoskeletal complaints in the two weeks prior to completing the survey, although none of the examined factors were associated with the complaints. It is notable, however, that 82% of the students reported spending 0-6 hours/day using a computer, with almost 28% reporting 4-6 hours/day of usage. Eleven percent of the participants reported using the computer more than 8 hours/day. Of those students who use a laptop computer for all computer use, 90.1% reported musculoskeletal complaints. The students reported that they did not experience job strain. Further studies should be performed using a survey specifically intended for college students. CONCLUSION: The majority of female college students in this study reported musculoskeletal discomfort during or after computer use. Although a statistical correlation could not be made, students using laptop computers reported a higher incidence of musculoskeletal symptoms than those using desktop computers. Additionally, female college students did not seem to experience job strain. Future research should continue on larger, more diverse samples of students to better understand the prevalence and contributors of musculoskeletal complaints, how college students experience job strain (stress), and whether these two factors are related.